Regional lymph node irradiation in locally advanced Merkel cell carcinoma reduces regional and distant relapse and improves disease-specific survival. (February 2021) - Andruska, Neal; Mahapatra, Lily; Brenneman, Randall J.; Huang, Yi; Paniello, Randal C.; Puram, Sidharth V.; Mansour, Mena; Rich, Jason T.; Baumann, Brian C.; Thorstad, Wade L.; Daly, Mackenzie D.
Highlights: Merkel cell carcinoma (MCC) often presents with regional lymph node involvement. Indications for regional lymph node radiotherapy (rLN-RT) aren't well established. rLN-RT reduced regional and distant relapse and improved disease-specific survival. Adjuvant nodal radiation therapy (AnRT) improved all outcome-related endpoints. Patients with ENE, ≥2 positive nodes, or bulky nodes benefited the most from AnRT. Abstract: Background: One-third of patients with Merkel cell carcinoma (MCC) present with locally advanced disease involving the regional lymph nodes, but indications for regional lymph node radiation therapy (rLN-RT) are not well established. Materials and methods: 72 patients with locally advanced MCC were retrospectively reviewed. Regional lymph nodes were addressed with observation, lymph node dissection (LND) alone, definitive nodal radiotherapy (DnRT), or LND plus adjuvant nodal radiotherapy (AnRT). Cox regression was used to compare treatment modalities in terms of regional recurrence-free survival (RRFS), distant recurrence-free survival (DRFS), disease-free survival (DFS) and disease-specific survival (DSS). Results: rLN-RT, including both DnRT and AnRT, improved RRFS (Hazard ratio (HR): 0.07, 95% confidence interval (CI): 0.01–0.40, p  = 0.003), DRFS (HR: 0.28, CI: 0.11–0.76, p  = 0.01), DFS (HR: 0.23, CI: 0.09–0.58, p  = 0.002), and DSS (HR: 0.23, CI: 0.06–0.90, p  = 0.03). AnRT improved DFS and DSS in high-risk subgroups (e.g., extranodal extension (ENE), ≥ 2 positive lymph nodes, or bulkier lymph nodes). The benefit of AnRT increased with higher disease burden. After controlling for these adverse factors, AnRT significantly improved RRFS (HR: 0.04, CI: 0.01–0.37, p  = 0.004), DRFS (HR: 0.14, CI: 0.04–0.50, p  = 0.003), DFS (HR: 0.09, CI: 0.02–0.33, p  < 0.001), and DSS (HR: 0.21, CI: 0.05–0.89, p  = 0.03). Conclusion: rLN-RT, including both DnRT and AnRT, reduces relapse and death from MCC in patients with node-positive disease. AnRT is particularly beneficial for patients with ENE, multiple involved lymph nodes, or larger nodal foci of disease. These results argue for more liberal use of nodal RT for MCC patients who present with node-positive disease.